Enantio- and diastereoselective Michael additions of C-succinimidyl esters to nitro olefins using cinchonine-derived bifunctional organocatalysts - Jakubec, P; Cockfield, D; Hynes, P; Cleator, E; Dixon, D (2011)
A novel bifunctional organocatalytic Michael addition of a succinimide-derived pronucleophile to nitro olefins is described. The use of a range of nitro olefins afforded Michael adducts containing contiguous quaternary and tertiary stereogenic centres in high enantioselectivities and moderate diastereoselectivities. © 2011 Elsevier Ltd. All rights reserved.